Migraine and Ischemic Stroke: A Mendelian Randomization Study - Shu, Mei-Jun; Li, Jia-Rui; Zhu, Yi-Cheng; Shen, Hang (Neurology and therapy, 2022)
Introduction Previous epidemiological studies have found an increased risk for ischemic stroke in patients with migraine; however, the evidence for a causal relationship between migraine and ischemic stroke is scarce. This study aims to explore the potential causal relationship between migraine and ischemic stroke and its subtypes [including large artery stroke (LAS), small vessel stroke (SVS), and cardioembolic stroke (CES)]. Methods We used data on genetic variants associated with migraine identified from a genome-wide association study (GWAS) meta-analysis among 889,018 European ancestries. Summary data for ischemic stroke and its subtypes were obtained from the MEGASTROKE consortium including up to 438,847 participants. We performed two-sample Mendelian randomization (MR) analyses using the inverse-variance-weighted method as the primary approach. The MR-Egger, weighted median, simple median, simple mode, and weighted mode methods were also conducted as sensitivity analyses to determine the robustness of our results. Results We failed to detect statistically significant associations between migraine and ischemic stroke (OR, 0.935; 95% CI 0.851–1.027; P = 0.159) and its subtypes (LAS: OR, 0.818; 95% CI 0.692–0.967; P = 0.018) (SVS: OR, 0.935; 95% CI 0.781–1.119; P = 0.460) (CES: OR, 1.015; 95% CI 0.867–1.189; P = 0.850). The results were consistent with the sensitivity analyses. Conclusions By conducting a series of causal inference approaches, this study supports no causal effect of migraine on ischemic stroke and its subtypes.